Morphometric and morphological changes in the spleen in the context of experimental modeling of chronic kidney failure - Sherzod Shodulloyevich Sobirov (Science and Education, 2025)
The article explores the structural alterations in the spleen resulting from chronic kidney failure using experimental animal models. Through detailed histological and morphometric analyses, the study reveals significant changes in spleen architecture, including lymphoid depletion, vascular alterations, and disruption of the white-to-red pulp ratio, which correlate with the progression of CKF. These findings suggest that chronic renal dysfunction exerts a systemic impact extending to lymphoid organs, underscoring the spleen’s potential role in the immunopathogenesis associated with CKF and highlighting its value as a secondary indicator in experimental nephrology.